Do religious fictionalists face a problem of evil? - Deng, Natalja ca. 20./21. Jh. (Religious studies, 2024)
Much of the literature on religious fictionalism has emphasized that religious fictionalists employing a theistic fiction cannot just leave evil out of the fiction, and that on the contrary, they face worries that very closely parallel the worries raised by the problem of evil. This article argues that when religious fictionalism is construed most charitably, these worries do not arise. It explores three fictionalist approaches to evil (Excision, Completeness, and Inconsistency), shows that each can serve religious fictionalist ends, and recommends a pluralist stance towards them.